Evaluation of jump protocols to assess leg power and predict hockey playing potential - Burr, J. F.; Jamnik, V. K.; Dogra, S.; Gledhill, N. (The Journal of Strength and Conditioning Research, 2007)
The purposes of this study were (a) to determine the measurement device and jumping protocol most appropriate for testing the leg power of elite hockey players and (b) to assess the relationship of leg power measurements to hockey playing ability as indicated by draft selection order. Comparisons were made of leg power measurements from the top 95 players entering the National Hockey League Entry Draft using 2 devices (Vertec and Just Jump) and 2 jump protocols (countermovement and squat). Players' leg powers were ranked from highest to lowest power using each device and protocol and were correlated with draft selection order. Vertec leg power measurements were highest (5,511-5,631 W), but there were no significant differences in power between the 2 jumping protocols on either device. Vertec squat jump provided the highest correlation (0.47) between leg power ranking and selection order and was judged to most closely approximate the full-body coordinated movements involved in hockey. The Vertec device using a squat jump protocol is most appropriate for coaches and fitness specialists to use when evaluating hockey potential based on the off-ice leg power measurements of elite hockey players.